PSIKOTERAPI ISLAMI TERHADAP PSIKOPATOLOGI (Perspektif Psikologi Pendidikan Islam) - Evita Yuliatul Wahidah (Universitas Muhammadiyah Ponorogo, 2016)
In a review of psychology, psychopathology can be started from three assumptions. First, the Freudian assumed that the human soul was basically born in sickness, evil, negative / destructive. To be positive, it need companion ways that are impersonal and directive / directing. Second, as a behaviorist, Skinner assumed that the human soul was born in neutral (not sick and unhealthy), where the environment plays a role in determining the direction of its development. Third, Maslow and Rogers as a humanistic figure assumed that the human soul was born in a state of conscious, free, responsible and guided by positive forces emanating from itself to the expansion of all human potential to its fullest. Whereas in Islamic studies of psychopathology can be divided into two categories, namely the worldly, as has been formulated by contemporary psychology, and the hereafter. This paper attempts to explain kinds of psychotherapy according to the study of Islam and how Islam is doing its part in the psychotherapy world and ukhrowi psychopathology. Discussion of Islam against psychopathology of psychotherapy becomes important. In addition to see the growing of Islamization method, as well as to explore therapist aspects in Islam based on the Qur'an and Hadith. The Islamic Psychotherapy is also to provide an alternative to the criticisms made against modern psychology that break away from the values of divinity. This paper begins his discussion of the notion of Psychopathology, Islamic psychotherapy understanding and the existing concept of the theories.